La València quatrecentista a través dels ulls d'un notari: les notícies de Jaume Vinader. - FAJARDO PAÑOS, JAVIER; FAUS FAUS, MIQUEL (Scripta, 2019)
This paper presents a study and a complete edition of all the news written by valencian notary Jaume Vinader, preserved into his notarial books during the major part of 15th century (1419-1467). These little chronicles allow us to penetrate in some of the most important incidents of the century through the eyes and the memories of a notary, that is, through a different perspective from traditional ways based on sources emanated from the contemporary powe « « r. In short, the case we introduce open a new perspective for notarial sources' study, normally used for economic and social studies.